Impact of the COVID-19 Pandemic on the Psychological Distress of Medical Students in Japan: Cross-sectional Survey Study - Nishimura, Yoshito; Ochi, Kanako; Tokumasu, Kazuki; Obika, Mikako; Hagiya, Hideharu; Kataoka, Hitomi; Otsuka, Fumio (JMIR Publications, 2021)
BackgroundThe COVID-19 pandemic has negatively affected medical education. However, little data are available about medical students' distress during the pandemic. ObjectiveThis study aimed to provide details on how medical students have been affected by the pandemic. MethodsA cross-sectional study was conducted. A total of 717 medical students participated in the web-based survey. The survey included questions about how the participants' mental status had changed from before to after the Japanese nationwide state of emergency (SOE). ResultsOut of 717 medical students, 473 (66.0%) participated in the study. In total, 29.8% (141/473) of the students reported concerns about the shift toward online education, mostly because they thought online education would be ineffective compared with in-person learning. The participants' subjective mental health status significantly worsened after the SOE was lifted (P<.001). Those who had concerns about a shift toward online education had higher odds of having generalized anxiety and being depressed (odds ratio [OR] 1.97, 95% CI 1.19-3.28) as did those who said they would request food aid (OR 1.99, 95% CI 1.16-3.44) and mental health care resources (OR 3.56, 95% CI 2.07-6.15). ConclusionsGiven our findings, the sudden shift to online education might have overwhelmed medical students. Thus, we recommend that educators inform learners that online learning is not inferior to in-person learning, which could attenuate potential depression and anxiety.